Regenerative application of stromal vascular fraction cells enhanced fat graft maintenance: clinical assessment in face rejuvenation. (1st December 2020) - Gentile, Pietro; Sterodimas, Aris; Calabrese, Claudio; De Angelis, Barbara; Trivisonno, Angelo; Pizzicannella, Jacopo; Dionisi, Laura; De Fazio, Domenico; Garcovich, Simone
ABSTRACT: Objectives: The aim of this study was to evaluate the safety and efficacy of the use of FG-SVFs in face rejuvenation for esthetic improvement. Methods: 33 female patients affected by face's soft-tissue defects with loss of volume, study group (SG), were treated with FG-SVFs, comparing results with a control group (CG) (n = 30) treated with fat graft not enhanced (FG). Clinical evaluation, a photographic assessment, magnetic resonance imaging (MRI), and ultrasound (US) were performed. Post-operative follow-up was performed at 1, 3, 7, 12, 24, 48, weeks, and then annually. Results: SG patients showed 61% maintenance of the contour restoring and of volume after 3 years compared with the CG treated with FG, who showed 31% maintenance. 60.7% (n = 20) of SG patients, presented an increase of 6.6 mm in the soft tissue volume after 36 months, which was reported in only 33, 3% (n = 10) of the CG. Volumetric persistence in the SG was higher than that in the CG (p <. 0001 vs. CG). MRI and US moreover confirmed the absence of important side effects, as fat necrosis, and cytosteatonecrotic areas. Conclusions: The use of FG-SVFs was safe and effective in this series of a case treated.